Cost comparison between the recovery of chromium from the wastewater of metal finishing industry using ion exchange and chromium disposal using chemical precipitation. - Dayoan, Teodora C. (Animo Repository, 2000)
To minimize the presence of the hazardous metal in the environment, water contaminated wit hexavalent chromium from metal finishing industry may be removed and recovered through the use of ion exchange resins or could be disposed by chemically reducing it to the trivalent chromium state that is less toxic. The reduction is performed by chemical precipitation using sodium metabisulfite as the reducing agent. Treating waste metal is practiced to prevent water pollution and to possibly recover important metals. This study compares the cost of recovering chromium using the ion exchange method and the cost of reduction and disposal of the reduced trivalent chromium through chemical precipitation. The investigation of the amount for chromium to be recovered in hexavalent form using the ion exchange method as well as the amount of chromium that could be reduced by chemical precipitation using sodium metabisulfite as reducing agent were conducted. The ion exchange method utilizing Amberlite IR120 Na as cation and Amberlite IRA402 Cl as anion was conducted by batches at sample wastewater concentration of 100, 150 and 250 mg/L of Cr+6 and flow rates of 200, 250 and 300 ml/min. The same concentration of Cr+6 was used in the chemical precipitation and the experimentation was also done by batches. The pH reduction of hexavalent chromium to trivalent chromium ranged from 2.0-3.0 and the pH used to precipitate the reduced chromium ranged from 9.2-9.8. Wastewater sample was taken from a metal finishing plant located in Paranaque Metro Manila. The sample was take from the drag-out tank that was found to contain 80,000 mg/L. The ion exchange method gave a 99.99 percent efficiency in recovering the chromic acid from the wastewater giving an effluent concentrations of <0.01 mg/L of Cr+6. The results obtained in the chemical precipitation method gave an effluent concentrations of <0.01 to 0.047 mg/L of Cr+6. An economic study was conducted to compare the cost of recovering the hexavalent chromium from the rinse waters through the ion exchange method and using the traditional method of chemical precipitation using sodium metabisulfite as reducing agent and disposing the reduced chromium in its insoluble hydroxide form. The computation were based on one day of operation with the volume of 3,000 liters of rinse water per day. The chromate content of the waste water is 250 mg/L which is equivalent to 750 grams chromic acid per day.The study showed that the use of ion exchange method gave a total annual costs of PhP 2,816,781.31 while the total annual costs for the chemical precipitation amounted to PhP 5,568,084.70. This gave a saving of PhP 2,751,303.39. The estimated fixed-capital investment for the ion exchange system required PhP 5,278,832.00 while the chemical precipitation method needed only PhP 347,900.00. The computed percent return of investment in favor of the ion exchange method is 55.80 percent.